Intonation in Four Indian Languages Under Five Emotional Conditions - Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
The changes in pitch which occur within a sentence are  not hapazard variation.The pattern of variation, the rules of changes, are highly organised. Their intricacy is so great that, although one speaks his language with little effort, their analysis is extremely difficult and may induce one to conclude that no actual organization or rules are present, but that people  use pitches by whim and fancy.  In each language, however,  the use of pitch fluctuation tends to become  semi standardized, or  formalized,  so that all speakers of the language use basic pitch sequences in similar ways under similar circumstances. These abstracted characteristic sentence melodies may be called "Intonation contours", '(Pike, 1945)